A Ag synchronously deposited and doped TiO2 hybrid as an ultrasensitive SERS substrate: a multifunctional platform for SERS detection and photocatalytic degradation. Issue 22 (23rd May 2018) - Yang, Libin; Sang, Qinqin; Du, Juan; Yang, Ming; Li, Xiuling; Shen, Yu; Han, Xiaoxia; Jiang, Xin; Zhao, Bing
Abstract : We proposed a Ag synchronously deposited and doped TiO2 hybrid as a dual-function platform for ultrasensitive SERS detection and efficient photocatalytic degradation. Abstract : Ag simultaneously deposited and doped TiO2 (Ag–TiO2 ) hybrid nanoparticles (NPs) were prepared via a sol–hydrothermal method, as both a sensitive surface-enhanced Raman scattering (SERS) substrate and a superior photocatalyst for the first time. Ag–TiO2 hybrid NPs exhibit excellent SERS performance for several probe molecules and the enhancement factor is calculated to be 1.86 × 10 5 . The detection limit of the 4-mercaptobenzoic acid (4-MBA) probe on the Ag–TiO2 substrate is 1 × 10 −9 mol L −1, which is four orders of magnitude lower than that on pure TiO2 as a consequence of the synergistic effects of TiO2 and Ag. This is the highest SERS sensitivity among the reported semiconductor substrates and even comparable to noble metal substrates, and a SERS enhancement mechanism from the synergistic contribution of the semiconductor and noble metal was proposed. And importantly, the Ag–TiO2 hybrid shows excellent photocatalytic degradation activity for the detected species under UV light irradiation at lower concentration conditions, even for the hard to degrade 4-MBA molecule. This makes the Ag–TiO2 hybrid promising as a dual-function platform for both highly sensitive SERS detection and photocatalytic degradation of a pollutant system. Moreover, it also proves that the Ag–TiO2 hybrid can serve as a promising recyclable SERS-active substrate by virtue of its photocatalytic self-cleaning properties for some specific applications, for instance comparative studies of different species on the same SERS platform, in addition to the economic benefit.